All Love Begins and Ends Here - Sagüés, Usoa García (Journal of the Motherhood Initiative for Research and Community Involvement, 2025)
I am an artist currently studying textiles at the Royal College of Art. My practice focusses on soft sculpture to tell an alternative motherhood story. This article offers meaningful glimpses into motherhood through original artworks from a recent college exhibition with the same title and supported by our student union, for which I was awarded to curate in March 2025. The open call asked artists to respond to a quote from Hettie Judah in her 2024 book Acts of Creation: “Long taboo, the realities of motherhood are now the subject of urgent discussion.” I believe I have never added as much value as being a mother. However, I have also never felt as lonely and overlooked. Through my curatorial choices, I wanted to highlight this paradox of motherhood and show that I am not alone. While the virgin and child is one of the great subjects of European art, there is more to be expressed about motherhood as a lived complex experience, including themes of identity change, blurred boundaries, sacrificing the self, and retaining strength, patience, and grounding while fighting solitude, depression, worthlessness, and fear, as well as being often flooded with pride and joy. The show successfully explored the gifts and struggles of mothers —and of not becoming a mother—through fourteen works by twelve artists from programs across the college. To the collective world, mothers are only mothers but to so many individually they make the world. It was a pleasure to see the audience immersed in the artists’ stories. Their interest prompted me to write this article to sustain discussion around motherhood.